2004
DOI: 10.1002/cne.20354
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the vesicular glutamate transporters during development indicates the widespread corelease of multiple neurotransmitters

Abstract: Three closely related proteins transport glutamate into synaptic vesicles for release by exocytosis. Complementary patterns of expression in glutamatergic terminals have been reported for VGLUT1 and VGLUT2. VGLUT3 shows expression by many cells not considered to be glutamatergic. Here we describe the changes in VGLUT expression that occur during development. VGLUT1 expression increases gradually after birth and eventually predominates over the other isoforms in telencephalic regions. Expressed at high levels s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
225
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(251 citation statements)
references
References 83 publications
(134 reference statements)
24
225
2
Order By: Relevance
“…This finding is in agreement with previous anatomical studies (8,21), which could not demonstrate the presence of VGLUT1-3 in the neuromuscular junction. However, a recent study has shown that VGLUT3 is expressed in proximity to the endplates in skeletal muscles (27). At the moment, there is no explanation for the discrepancies between different studies.…”
Section: Discussionmentioning
confidence: 93%
“…This finding is in agreement with previous anatomical studies (8,21), which could not demonstrate the presence of VGLUT1-3 in the neuromuscular junction. However, a recent study has shown that VGLUT3 is expressed in proximity to the endplates in skeletal muscles (27). At the moment, there is no explanation for the discrepancies between different studies.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies demonstrating VGluT-2 immunostaining in motoneuron collateral axons projecting to layer VII of the spinal cord (28,32) confirmed the lack of VGluT-2 and glutamatergic transmission in the cholinergic projections to the NMJ. Furthermore, studies on VGluT-3 expression at the skeletal muscle endplates gave contradictory results (33,34). The difficulty in demonstrating VGluT expression at the cholinergic synapses indicates that mechanisms responsible for the high concentration of glutamate at the NMJ still need to be clarified or their identification requires more sensitive investigation tools.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian development, VGluT1 expression increases gradually after birth and predominates over the other isoforms in telencephalic regions. In contrast, VGluT2 is expressed at high levels shortly after birth and declines with age (Boulland et al, 2004;Nakamura et al, 2005). In the present study, we only investigated the changes in VGluT1-immunopositive synapse densities.…”
Section: Saturation Of Vglut1-and Vgat-immunopositive Synaptic Densitmentioning
confidence: 98%